ANALISIS PENERAPAN IDENTIFIKASI PASIEN DENGAN DUA IDENTITAS TERHADAP KUALITAS KESELAMATAN PASIEN DI RUMAH SAKIT : SCOOPING REVIEW - Ellyda Septiani Pramita; Oktora Dwi Putri Ramadhanti; Andi Irun Fitra Dewi Pagala; Ninis Saputri; Tri Regita Alfiadji Paputungan; Iwan Rifai Alam Siregar (HEALTH CARE: JURNAL KESEHATAN, 2025)
Background: Patient safety is a major concern in healthcare systems worldwide, as preventable medical incidents remain common in hospital settings. Patient misidentification is a leading cause of medication errors, incorrect procedures, and diagnostic delays, posing serious risks to patient safety and quality of care. Purpose: This scoping review aims to analyze the implementation of dual patient identification and its contribution to improving patient safety quality in hospitals. Methods: This study employed a scoping review approach using the Arksey and O’Malley framework and PRISMA guidelines, with literature searches conducted through PubMed, Scopus, and ScienceDirect databases for articles published between 2020 and 2024. Eight eligible articles were analyzed narratively. Results: The findings indicate that the implementation of dual patient identification, commonly using full name and date of birth, improves patient identification accuracy, reduces the risk of medical errors, and strengthens the culture of patient safety. The use of supporting technologies such as barcode wristbands and electronic medical records, combined with ongoing training for healthcare professionals, increases compliance with patient safety standards. Conclusion: Dual patient identification significantly contributes to improving patient safety quality in hospitals; future studies are recommended to explore long-term effectiveness, cost implications, and barriers to implementation across diverse healthcare settings.